Distribution of HBV genotypes from two blood transfusion centers in western Saudi Arabia. (May 2014) - Bajrai, Leena H; Kumosani, Taha; El-Kafrawy, Sherif; El-Daly, Mai; Hindawi, Salwa; Ashshi, Ahmed; Azhar, Esam I
Aim: To determine the distribution of HBV genotypes among HBsAg-positive blood donors in Makkah and Jeddah.Materials & methods: A total of 158 volunteered HBsAg-positive male blood donors donated blood samples at two transfusion centers in western Saudi Arabia. RFLP digestion was performed on 83 PCR products of the S gene. A subset of 77 positive samples were sequenced and aligned with reference Genbank sequences.Results: RFLP showed the following genotype distribution: 71 (85.6%) D; two (2.4%) E; one (1.2%) A; one (1.2%) B; one (1.2%) C; five (6.0%) untypable; one (1.2%) mixed genotypes D+A; and one (1.2%) mixed genotype D+C. Seventy-seven samples were genotyped by sequencing as follows: 73 (94.8%) D, three (3.9%) E; and one (1.3%) A. The study showed that there is concordance in the results of RFLP and sequencing in 67 samples and discrepancy in ten samples: genotypes B, genotype C, one of genotype E and dual genotypes by RFLP could only been detected as genotype D by sequencing. Sequencing showed the RFLP untypable samples as genotypes D and E.Conclusion: HBV type D is the most prevalent genotype in western Saudi Arabia. RFLP is a reliable tool for predicting genotype D in Saudi population.